Effects of Weather, Time, and Pollution Level on the Amount of Particulate Matter Deposited on Leaves of Ligustrum lucidum - Huixia Wang; Hui Shi; Yanhui Wang (The Scientific World Journal)
This paper investigated the spatial and temporal variations in the amounts of PM accumulated on leaves of Ligustrum lucidum, a common evergreen tree species in North China. The effects of rainfall and wind on the amounts of PM deposited on foliage were also determined. The amounts of PM (g·m−2) retained by leaves of L. lucidum differed significantly among the sites (from 0.96 to 5.56) and over time (from 2.51 to 4.48). The largest amounts of PM on foliage of L. lucidum were observed on plants growing at the most polluted site. During the year, the highest and lowest accumulation of PM occurred in November and August, respectively. A considerable proportion of the accumulated PM on leaves was removed by rainfall events (28–48% of PM) and strong winds (27–36% of PM), and more precipitation or higher maximum wind speed could remove more PM from leaves. Rainfall removed mainly large and coarse particles, while fine particles adhered more strongly to the foliage. These results suggested that the effects of local weather conditions (e.g., rainfall, strong wind), different seasons, and pollution levels should be considered in evaluating total PM accumulation on leaves.